Transcription Factor-7-Like-2 (TCF7L2) in Atherosclerosis: A Potential Biomarker and Therapeutic Target - Li, Junyi; Zhou, Li; Ouyang, Xinping; He, Pingping (Frontiers in Cardiovascular Medicine, 2021)
Transcription factor-7-like-2 (TCF7L2), a vital member of the T-cell factor/lymphoid enhancer factor (TCF/LEF) family, plays an important role in normal human physiological and pathological processes. TCF7L2 exhibits multiple anti-atherosclerotic effects through the activation of specific molecular mechanisms, including regulation of metabolic homeostasis, macrophage polarization, and neointimal hyperplasia. A single-nucleotide substitution of TCF7L2, rs7903146, is a genetic high-risk factor for type 2 diabetes and indicates susceptibility to cardiovascular disease as a link between metabolic disorders and atherosclerosis. In this review, we summarize the anti-atherosclerosis effect and novel mechanisms underlying the function of TCF7L2 to elucidate its potential as an anti-atherosclerosis biomarker and provide a novel therapeutic target for cardiovascular diseases.